2017
DOI: 10.1016/j.neuron.2017.06.047
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Expression of VCAM1 in Radial Glial Cells Is Required for the Embryonic Origin of Postnatal Neural Stem Cells

Abstract: During development, neural stem cells (NSCs) undergo transitions from neuroepithelial cells to radial glial cells (RGCs), and later, a subpopulation of slowly dividing RGCs gives rise to the quiescent adult NSCs that populate the ventricular-subventricular zone (V-SVZ). Here we show that VCAM1, a transmembrane protein previously found in quiescent adult NSCs, is expressed by a subpopulation of embryonic RGCs, in a temporal and region-specific manner. Loss of VCAM1 reduced the number of active embryonic RGCs by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
64
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(67 citation statements)
references
References 61 publications
3
64
0
Order By: Relevance
“…We analyzed the molecular marker expression and apical surface sizes of 153–888 ventricular epithelial cells per time point (Figure 2A). In agreement with previous findings, we found that VCAM1 was expressed in the apical domain of many embryonic VZ cells (Figure 2A; Hu et al, 2017). During postnatal development, VCAM1 expression decreased in cells that continued to expand their apical domains (Figures 2A–2C).…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…We analyzed the molecular marker expression and apical surface sizes of 153–888 ventricular epithelial cells per time point (Figure 2A). In agreement with previous findings, we found that VCAM1 was expressed in the apical domain of many embryonic VZ cells (Figure 2A; Hu et al, 2017). During postnatal development, VCAM1 expression decreased in cells that continued to expand their apical domains (Figures 2A–2C).…”
Section: Resultssupporting
confidence: 93%
“…E1 cells also adhere to B1 cells in pinwheel cores. VCAM1 has been shown to be expressed on the apical domain of quiescent B1 cells (Kokovay et al, 2012; Codega et al, 2014; Hu et al, 2017), and blocking antibodies against VCAM1 destabilize junctional complexes and disrupt epithelial cytoarchitecture, resulting in a loss of pinwheels (Kokovay et al, 2012). However, the time at which VCAM1 function is necessary for the development of pinwheels, and the potential involvement of other adhesion molecules expressed by E1 cells, B1 cells, or both are not well understood.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To investigate whether reduced cell proliferation causes decreased pool of NSCs/NPCs, we performed IHC at both WT and AKH −/− SVZ niche with vascular cell adhesion molecule‐1 (Vcam1) (Figure a,a',e,e') that is involved in maintaining the quiescent state of NSCs to avoid premature neuronal differentiation (Hu et al, ; Kokovay et al, ). We also performed IHC with mammalian achaete‐scute homolog‐1 (Mash1) (Figure b,b',f,f') that plays dual role, where its oscillatory expression mode is involved in maintaining the proliferation of NPCs, while sustained expression mode promotes differentiation into neuronal lineages (Tang, ).…”
Section: Resultsmentioning
confidence: 99%